Aminobisphosphonate‐associated orbital and ocular inflammatory disease. Issue 5 (28th February 2019) - Keren, Shay; Leibovitch, Igal; Ben Cnaan, Ran; Neudorfer, Meira; Fogel, Ortal; Greenman, Yona; Shulman, Shiri; Zur, Dinah; Habot‐Wilner, Zohar
Abstract: Purpose: Aminobisphosphonates may cause orbital/ocular inflammation. Awareness of the clinical presentation and disease course is crucial. The purpose of this study was to analyse demographics, clinical presentation, disease course and treatment of aminobisphosphonate‐associated orbital/ocular inflammation in a large series of patients. Methods: A retrospective study of patients with aminobisphosphonate‐associated orbital/ocular inflammation and a literature review to differentiate disease presentation and course between various aminobisphosphonates. Results: Eight patients from our institution (6 women and 2 men, median age 62 years) were included. The used drugs were zoledronate, alendronate and risedronate. The most common clinical presentation was conjunctival hyperaemia/chemosis. Scleritis was the most common manifestation, followed by diffuse orbital inflammation and anterior uveitis. Ultrasound aided in diagnosis in all our patients. The aminobisphosphonate was halted in all patients, and some patients had anti‐inflammatory treatment. Literature review included 68 patients (83 eyes), of them the most abundant drugs causing orbital/ocular inflammation were pamidronate (38 eyes) and zoledronate (35 eyes). Overall, among 76 patients, all drugs induced orbital disease, while uveitis was induced mostly by zoledronate and pamidronate, less by alendronate and not found among risedronate users. Time interval from drug administration to symptoms was hours to 28 days. Resolution was achieved in all patients, after 1–60 days from disease presentation, and the longer resolution period was found among alendronate users. Conclusion: Orbital/ocular inflammation was mostly caused by intravenous aminobisphosphonates. Uveitis was not induced by risedronate. The putative aminobisphosphonate should be halted at the onset of orbital/ocular involvement and prognosis is favourable.